Study of the Implementation of Socratic Dialogue at History of Physics Course - Moch Yusuf Efendi; Tsung-Hui Cheng; Elok Halimah Sa'diyah; Desi Wulandari; Ahmad Qosyim; Nadi Suprapto (Studies in Philosophy of Science and Education, 2020)
Having the development of learning materials of the history of physics with Socratic learning dialogue, we implemented them to the two classes in a public university in Indonesia. The materials consisted of a lesson plan, student worksheets, evaluation sheets, and rubrics that fulfill the criteria of construct, content, and empirical validity. However, the discussion of this paper focused on the results of empirical validity. Learning materials were trialed and tested on a limited participant (10 university students from a public university in Surabaya - S), then the real classes included 40 students from a public university in Surabaya, Indonesia- S1 and S2 (20 students for each class). The data analysis technique used a descriptive statistical analysis with percentages and logical analysis. The research findings included: 1) the student's assessment of the learning materials (especially the handout and student worksheet) were categorized as good, 2) the feasibility of the learning materials during the real teaching activities obtained: the implementation of history of physics learning at S1 and S2 for each item was a quite good category, and 3) assessment of critical thinking students who are oriented Socratic dialogue showed that over 60% and 70% of S1 and S2 student answers lead to Socratic thinking, respectively. The implication of the study is the availability of physics history learning materials that are ready to be used in conducting lectures in the following semester.